MEDIASI DALAM PENYELESAIAN SENGKETA MEDIS SEBAGAI UPAYA PERLINDUNGAN PASIEN - Anggraeni Endah Kusumaningrum (JURNAL ILMIAH HUKUM DAN DINAMIKA MASYARAKAT, 2016)
Legal relationship between doctor and patient in health care is often tinged with neglect of the rights of patients, causing a conflict or dispute. Mediation is a form of alternative dispute resolution (ADR) or alternative dispute resolution outside the court. Mediation is considered more profitable the parties since the mediator has no authority to decide, but only as a mediator of the agreement by the parties. The advantages of using mediation path is a simple procedure, effective, inexpensive, decisions are still in control the parties to the dispute, even though mediation is not a panacea to overcome distortions paradigm of litigation and can not be applied to all disputes.